2018
DOI: 10.1021/acs.jchemed.7b00958
|View full text |Cite
|
Sign up to set email alerts
|

Action Research: Integrating Chemistry and Scientific Communication To Foster Cumulative Knowledge Building and Scientific Communication Skills

Abstract: Collaboration between chemistry lecturers and literacy lecturers led to the development and implementation of an interdisciplinary project with the object of addressing two pertinent challenges in chemistry education. The first challenge is the tendency of students to approach different topics in science as separate units of knowledge, which hinders cumulative knowledge building. The second challenge is the effective incorporation of scientific communication skills into science curricula. In the course of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…International Journal of Instruction, October 2019 • Vol.12, No.4 independence in planning and implementing an investigation plan leads to them acting as initiators in terms of supporting the development of their own thinking and communication skills (King et al, 2018;Rootman-le Grange & Retief, 2018;Velasco et al, 2016). When conducting an investigation, students are more familiar with the procedures that they followed, thus making it easier for them to explain to the participants in the discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International Journal of Instruction, October 2019 • Vol.12, No.4 independence in planning and implementing an investigation plan leads to them acting as initiators in terms of supporting the development of their own thinking and communication skills (King et al, 2018;Rootman-le Grange & Retief, 2018;Velasco et al, 2016). When conducting an investigation, students are more familiar with the procedures that they followed, thus making it easier for them to explain to the participants in the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…When conducting an investigation, students are more familiar with the procedures that they followed, thus making it easier for them to explain to the participants in the discussion. The inquiry approach is not only beneficial for the students, but also useful for the lecturers in that it allows them to design better learning, modify more interesting inquiry procedures, and establish more intense communication with students (Burnham, 2013;Lechtanski, 2001;Rootman-le Grange & Retief, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The literature surrounding chemical communication pedagogy is diverse. However, efforts to improve written and oral communication skills have followed four general and broad approaches, which are sometimes presented in a hybrid form: (1) the incorporation of technical writing with chemical literacy, 66 77 in first-year courses, 39 , 66 , 67 , 78 83 stand-alone classes, 27 , 43 , 69 , 79 , 84 96 and/or discipline specific courses; 70 , 97 115 (2) laboratory experiments; 21 , 26 , 32 , 59 , 69 , 107 , 116 127 (3) critical thinking exercises; 3 , 13 , 26 , 117 , 128 143 and (4) research experiences. 134 , 144 155 Despite the community’s best efforts, a host of factors, which were identified early on, continue to present significant barriers for engaging and enhancing the communication skills of undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…At the end, students splice the knowledge generated from each phase into a single cohesive and meaningful scientific story, which is communicated both orally and in writing. In this report, we specify how we have leveraged the scientific method along with the community’s reports on technical writing for chemical literacy, 27 , 39 , 43 , 66 115 , 119 laboratory experiments, 21 , 26 , 32 , 59 , 107 , 116 127 , 173 175 critical thinking exercises, 3 , 13 , 26 , 117 , 128 143 and research experiences 146 155 to create a unique protocol to enhance the communication skills of undergraduates via individual one-on-one mentoring. This has been applied to our regional summer research program of roughly 35 students per year.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of chemistry education with other disciplines is a critical need when solving some of these larger challenges of design and use (1)(2)(3)(4)(5). Research has shown that scientific learning and critical thinking skills increase in students when technical content connects together sub-disciplines focused on interdisciplinary teamwork and research, repeats a set of core concepts within different contexts, incorporates inquiry-based methodology into lecture courses, involves students in design and production processes, and integrates advanced technology into learning environments (6)(7)(8)(9)(10)(11). Additionally, new pedagogical models are being explored to expand the scientific knowledge and critical thinking of scientists participating in academic and professional development learning experiences, especially for chemists and other health scientists who are working to promote the science of sustainability and the elimination of health disparities (1,3,6).…”
Section: Introductionmentioning
confidence: 99%